Phân huỷ 2,4,6-trinitrotoluen (TNT) trong chất thải rắn bằng phương pháp vi sinh hai giai đoạn - Thảo, Phạm Mạnh; Khuê, Đỗ Ngọc; Cường, Phạm Kiên; Minh, Đỗ Bình (Vietnam Journal of Chemistry, 2014)
A method for biodegrading 2,4,6-trinitrotoluene (TNT) as contaminant in solid waste by treatment of the contaminated waste under anaerobic using natural microorganisms is disclosed. Dry solid waste was first converted into a fluid medium by addition of water with a source of carbohydrate such as starch, potato processing waste, sewage sludge... The mixture was maintained in anaerobic condition and natural microorganisms fermented the carbohydrate and exhausted the oxygen in the fluid medium thereby rendering the slurry anaerobic which lowered the redox potential of the environment and promoted degradation of  TNT in the followed stage. Anaerobic conditions were preferably determined via a potentiometric measurement, where a redox potential of -200 mV or less indicated strict anaerobic conditions. In the subsequent anaerobic stage, an inoculum of a mixed population of anaerobic microorganisms completed the mineralization of TNT, using the remaining carbohydrate as a carbon and energy source. Microbial activity can assist degradation of organic contaminants either directly by enzyme production, or indirectly, by maintaining the reduction conditions of the environment and thereby enhancing the inorganic and biochemical mechanisms. Bench scale experiment was conducted to assess the rate and extent of TNT biodegradation. Results indicated that after 6 to 7 weeks incubation the concentration of TNT reduced greater than  95% from 277 mg.kg-1 at the initial to below 13 mg.kg-1.